Peningkatan Literasi Keuangan Siswa SMA melalui Program Edukasi sebagai Upaya Mengurangi Perilaku Konsumtif - Rahmadewi, Idayu; Inawati, Wahdan Arum; Nusuki, Ina (Edumedia Solution, 2026)
The lack of financial literacy among the younger generation is a serious obstacle to realizing the vision of Indonesia's Golden Generation 2045. Increasingly easy access to digital financial services, the proliferation of electronic transactions, and the increasing willingness to borrow make teenagers vulnerable to consumer behavior and poor financial decision-making. This phenomenon emphasizes the urgency of instilling financial literacy education starting in secondary education. This community service activity was held to strengthen students' knowledge and understanding of wise financial management through a financial literacy education program at SMA Edu Global, Bandung City. The method used was interactive counseling that included a pre-test, material presentation, discussion sessions, educational games, a post-test, and participant satisfaction evaluation. This activity was attended by 136 students, and the results showed a significant increase in answer scores from 400 points in the pre-test to 412 points in the post-test. In addition, a satisfaction survey recorded that 71.25% of participants agreed or strongly agreed that this activity was beneficial, the material was easy to understand, and it was worth holding regularly. These findings confirm that financial literacy education effectively strengthens participants' basic understanding of financial management while building awareness of the importance of responsible financial behavior. It is recommended that such programs be implemented on an ongoing basis as part of efforts to improve the financial literacy of the younger generation.